Can glycated hemoglobin act as a reliable glycemic indicator in patients with diabetic chronic kidney disease? evidence from the Northeast of Thailand (Medical Journal of Indonesia, 2017)
Background: Chronic kidney diseases (CKD) is a common microvascular complication in patients with diabetes mellitus (DM) which requires adequate glycemic control. Glycated hemoglobin (HbA1c) is a conventional biomarker to estimate glycemic status, but its role in diabetic CKD patients is unclear. Therefore, this study aimed to determine whether patients with high HbA1c are associated to develop diabetic CKD. Methods: Data were obtained from a clinical registry of diabetic patients who were treated in a district hospital in the Northeast of Thailand. CKD was defined according to the estimated glomerular filtration rate (eGFR<60mL/min/1.73m2). Anthropometric and biochemical measurements of the patient were taken by review of medical records. Multiple logistic regression analysis was used to determine the likelihood of the association between HbA1c and CKD. Results: Among 4,050 participants, 1,027 (25.3%) developed diabetic CKD. Older age (adjusted odds ratio (AOR): 4.88, 95% confidence interval (CI): 3.71-6.42, p<0.05), female (AOR: 1.38, 95% CI: 1.05-1.73, p<0.05), and hypertension (AOR: 1.52, 95% CI: 1.21-1.91, p<0.05) were found as the risk factors of diabetic CKD. However, patients with high HbA1c (>6.5%) were negatively associated with diabetic CKD (AOR: 0.66, 95% CI: 0.51-0.86, p<0.05). Conclusion: This study found patients with higher HbA1c level were not associated with diabetic CKD. Therefore, using the conventional cut-off values of HbA1c in diabetic CKD patients may be problematic in the clinical settings. Enhanced detection of glycemic status in patients with diabetic CKD is warranted to improve the outcome.